Registros históricos y remanentes actuales de la biota autóctona del Partido de Lanús (Provincia de Buenos Aires) - Fernández, Sergio Nicolai (2022)
The Municipality of Lanús is located in the Province of Buenos Aires and constitutes the first case within the Gran Buenos Aires región where an almost total loss of natural green spaces is recorded. Only a few sectors remain, limited to railways (active or closed), some vacant lots and stretches of the rectified riverbank of the Matanza-Riachuelo river. On the other hand, there are few bibliographical references that provide concrete notions about the original natural landscape of this district, before the urban and manufacturing expansion, except for the accounts of the first explorers after the arrival of the Europeans. This work focuses on a historical compilation and field research, and aims to make known the natural landscapes and the biota that were deployed on the floodplain, ravines and slight hills of the Matanza River basin, as well as enumerate, locate and describe the few green spaces that still exist and are threatened. The records and data prepared by the authors, all of them from Lanús and its surroundings, intend to constitute a basis for the preservation of these areas before their total disappearance, to have testimonial and educational samples of the natural heritage of the Lanús district and to ecological restoration where circumstances make it possible.